Targeting autophagy in cancer stem cells as an anticancer therapy. (1st May 2017) - Lei, Yuanyuan; Zhang, Dan; Yu, Jin; Dong, Hui; Zhang, Jianwei; Yang, Shiming
Abstract: Cancer stem cells (CSCs), which comprise a small proportion of total cancer cells, have special capacities for self-renewal, differentiation and tumor formation. Currently, CSCs are regarded as the major cause of the failure in anticancer therapy, such as chemoresistance and/or radioresistance, tumor recurrence and metastasis. Autophagy, a process of cellular self-digestion and response to stress, has a role in tumor formation and progression, and it may play a dual role in CSCs-related resistance to anticancer therapy. Most researchers believe that autophagy contributes to stemness maintenance of CSCs and is responsible for the failure of anticancer therapy. Unexpectedly, several studies have also suggested that loss of stemness in CSCs could be mediated by autophagy. Here, we review the recent advances in CSCs and autophagy, especially analyze the complex relationship between them, and hope to apply this new knowledge to the strategies for anticancer therapy. Highlights: Autophagy may play a dual role in CSCs-related resistance to anticancer therapy. Autophagy could contribute to stemness maintenance of CSCs and is responsible for the failure of anticancer therapy. Loss of stemness in CSCs could also be mediated by autophagy.